Pejabat Pendidikan Daerah Segamat (PPD Segamat) / Syazwanie Safar - Safar, Syazwanie (Faculty of Business and Management, 2023)
This report will tell the story of my wonderful industrial training experience! I had done my practical training at the Pejabat Pendidikan Daerah Segamat, commonly known as PPD Segamat, which is located in Seaman, Johor. I have been put under the procurement and infrastructure unit, which is under the management sector. The PPD Segamat had 79 staff and was divided into 8 sectors, and also several units under some of the sectors. This industrial training report has six main contents, references, and appendices. The first main content is the student portal, which has the current resume template. The next section is going to talk about the company that is being selected for the industrial training, which is Pejabat Pendidikan Segamat. In this section, we will talk all about the PPD Segamat background, logo, services, and so on. Going to the next section, this section will talk about the training reflections of the industrial training student through the six-month period. It was about the experiences, tasks, roles, responsibilities, and benefits gained over six months in the PPD Segamat. While the next section is about the SWOT analysis of the PPD Segamat, which is the strengths, weaknesses, opportunities, and threats. Some of the SWOT analysis points are related to the PESTEL aspect of the PPD Segamat. Then, it will be followed by some suggestions to the PPD Segamat to improve their management. In the last main section, there will be the conclusion of doing the industrial training for six months in the PPD Segamat. Last but not least, there are also the references that were used in the industrial training report and some appendices during the industrial training as evidence.